1877 : America's year of living violently - Bellesiles, Michael A. (New York : New Press : Distributed by Perseus Distribution, 2010)
Describes a time of upheaval in America--when the country was in a deep economic depression, white supremacists roamed the South, and a nationwide railroad strike led to bloodshed--and discusses how the events of 1877 also fueled cultural and intellectual innovation.
On the edge of a volcano -- Seeking white unity -- Bringing order to the West -- The terror of poverty -- The great insurrection -- Homicidal nation -- Breaking the spell.
Includes bibliographical references and index.
Keywords: United States -- Civilization -- 1865-1918.; Social conflict -- United States -- History -- 19th century; Violence -- United States -- History -- 19th century; Racism -- United States -- History -- 19th century; United States -- Race relations -- History -- 19th century; United States -- Economic conditions -- 1865-1918.; Railroad Strike, U.S., 1877.; Civilization; Economic history; Race relations; Racism; Social conflict; Violence; United States; Unruhen; Gesellschaft; USA; United States -- Civilization; Social conflict -- United States -- History; Violence -- United States -- History; Racism -- United States -- History; United States -- Race relations -- History; United States -- Economic conditions; Strikes -- Railroads -- United States -- History; 1800-1918; History